Heterozygous mutations in the PALB2 hereditary breast cancer predisposition gene impact on the three‐dimensional nuclear organization of patient‐derived cell lines1. Issue 5 (23rd January 2013) - Wark, Landon; Novak, David; Sabbaghian, Nelly; Amrein, Lilian; Jangamreddy, Jaganmohan R.; Cheang, Mary; Pouchet, Carly; Aloyz, Raquel; Foulkes, William D.; Mai, Sabine; Tischkowitz, Marc
Abstract PALB2/FANCN is a BRCA1‐ and BRCA2‐interacting Fanconi Anemia (FA) protein crucial for key BRCA2 genome caretaker functions. Heterozygous germline mutations in PALB2 predispose to breast cancer and biallelic mutations cause FA. FA proteins play a critical role in the telomere maintenance pathway, with telomeric shortening observed in FA cells. Less is known about telomere maintenance in the heterozygous state. Here, we investigate the roles of PALB2 heterozygous mutations in genomic instability, an important carcinogenesis precursor. Patient‐derived lymphoblastoid (LCL) and fibroblast (FCL) cell lines with monoallelic truncating PALB2 mutations were investigated using a combination of molecular imaging techniques including centromeric FISH, telomeric Q‐FISH and spectral karyotyping (SKY). Mitomycin C and Cisplatin sensitivity was assayed via cellular metabolism of WST‐1. The PALB2 c.229delT FCL showed increases in telomere counts associated with increased mean intensity compared with two wild‐type FCLs generated from first‐degree relatives (P =1.04E‐10 and P =9.68E‐15) and it showed evidence of chromosomal rearrangements. Significant differences in centromere distribution were observed in one of three PALB2 heterozygous FCLs analyzed when compared with PALB2 wild‐type, BRCA1 and BRCA2 heterozygous FCLs. No significant consistently increased sensitivity to Mitomycin C or Cisplatin was observed in LCLs. Our results are suggestive of an altered centromere distribution profile and a telomere instability phenotype. Together, these may indicate critical nuclear organization defects associated with the predisposition to transformation and early stage development of PALB2‐related cancers. © 2013 Wiley Periodicals, Inc.